(untitled) (Journal of Ethics in Emerging Technologies & Society p-ISSN 3117-5996 and e-ISSN 3117-6003, 2025)
Large-scale IoT and smart city deployments – interconnected sensor networks, intelligent transport systems, smart energy grids, environmental monitoring platforms, and AI-integrated urban services – generate persistent data about citizens, urban behaviour, and community life at scales and with granularities that create profound ethical challenges around privacy, democratic governance, equity, and the appropriate role of technology in shaping urban experience. This paper proposes the Smart City and IoT Ethics Framework (SCIEF), a systematic analysis of six ethical challenge domains – surveillance and privacy, democratic governance deficit, urban equity and digital divide, commercial exploitation of public data, infrastructure resilience and safety, and environmental impact – applied to five smart city deployment domains: traffic and mobility, energy management, public safety, environmental monitoring, and citizen services. SCIEF introduces the Smart City Ethics Score (SCES) and evaluates ethical governance quality across 18 European smart city deployments. Key results: commercial data exploitation achieves the highest ethical concern rating (mean SCES = 0.124, worst governed); democratic governance deficit is the most prevalent challenge (present in 83.3% of deployments); privacy-by-architecture deployments achieve 48.4% lower surveillance concern scores. The framework provides smart city ethics governance guidance for municipalities and urban technology deployers.